Pattern of upper gastrointestinal diseases: an audit of 1000 cases based on endoscopic findings from a tertiary care hospital in Mysore - H. B., Shashikumar; B. S., Madhu; Harshini, Motati (International Surgery Journal, 2018)
Background: Fibreoptic endoscopy is a highly efficient diagnostic tool, which is now increasingly being used in the diagnosis of upper gastrointestinal diseases. This study has been carried out to evaluate the distribution of various upper gastrointestinal diseases based on endoscopic findings in a tertiary care hospital in Mysore. Methods: A cross-sectional study was conducted based on data from endoscopic register of 1000 subjects who underwent endoscopy for various upper gastrointestinal symptoms from 1st January 2017 to 31st December 2017(one year). Results: Mean age of the study population was 50.23 years (SD-15.46). Minimum age was 12 years and maximum was 88 years. About 44.7% of the study subjects belonged to 40-60 age group.61.6% of the study subjects were males. Most common indication was pain abdomen (32.1%) followed by dysphagia (22.2%). Of the 1000 study subjects 18.6% had normal findings. Most common finding was Gastritis / Duodenitis /Gastric erosions (28%). Malignant lesions were noted among 11.1%, of which esophagus and stomach are 5.4% and 4.9% respectively. Conclusions: Endoscopic diagnosis is useful for early detection of UGI diseases and helpful for their management.